Akta Perikatan Hibah dan Akta Kuasa Hibah dalam Sistem Hukum Pertanahan di Indonesia - Gangsar Prasetyo (Faculty of Law Universitas Islam Indonesia, 2023)
This research discusses how land law is regulated in Indonesia in regards to obligation deeds and power-granting deeds? and what is the validity of the transfer of land rights based on the obligation deed and power-granting deed? This is a normative juridical research using conceptual and statutory approaches that utilised secondary data which were then analyzed using a qualitative method, namely research procedures that produce descriptive data. The results of this research indicate that there is no article in a statutory regulation that specifically regulates the preparation of deeds of engagement and deeds of power of attorney. Therefore, the use of obligation deeds and power-granting deeds as support or bridge to the making of grant deeds by PPAT is permitted. The making of these two deeds is permitted as long as the process of making them complies with statutory regulations, including the Civil Code, UUJN, and UUJN Amendments. The validity of a transfer of land rights over a grant is influenced by whether or not the obligation deed or the power-granting deed is valid. Whether the obligation deed and power-granting deed are valid refers to ithe process of making them which must comply with Article 1320 of the Civil Code on the conditions for the validity of an agreement. This is because the obligation deed and power-granting deed can be categorized as agreementsKey Word: Deed, Grant Agreement, Grant Power of Attorney AbstrakPenelitian ini membahas bagaimana pengaturan hukum pertanahan di Indonesia tentang akta perikatan dan akta kuasa hibah? serta bagaimana keabsahan peralihan hak atas tanah yang didasari oleh akta perikatan dan akta kuasa hibah? Penelitian ini merupakan penelitian yuridis normatif dengan menggunakan pendekatan konseptual dan perundang-undangan, menggunakan data sekunder yang kemudian dianalisis dengan metode pendekatan kualitatif, yaitu tata cara penelitian yang menghasilkan data deskriptif. Hasil penelitian ini yaitu tidak ada pasal dalam suatu peraturan perundang-undangan yang mengatur khusus mengenai pembuatan akta perikatan dan akta kuasa hibah. Oleh karena itu maka penggunaan akta perikatan dan akta kuasa hibah sebagai penunjang atau jembatan menuju pembuatan akta hibah oleh PPAT diperbolehkan. Pembuatan kedua akta tersebut diperbolehkan selama dalam proses pembuatannya mematuhi peraturan perundang-undangan, diantaranya KUHPerdata, UUJN, dan UUJN Perubahan. Keabsahan suatu peralihan hak atas tanah hibah, dipengaruhi oleh sah atau tidaknya pembuatan akta perikatan atau akta kuasa hibah. Sah atau tidaknya akta perikatan dan akta kuasa hibah, apabila dalam proses pembuatannya memenuhi Pasal 1320 KUH Perdata tentang syarat sahnya perjanjian. Dikarenakan akta perikatan hibah dan akta kuasa hibah dapat dikategorikan sebagai perjanjian.Kata-kata Kunci: Akta, Perikatan Hibah, Kuasa Hibah